1999
DOI: 10.1177/030089169908500619
|View full text |Cite
|
Sign up to set email alerts
|

Primary Esophageal Lymphoepithelioma

Abstract: Lymphoepitheliomas are extremely rare outside the nasopharynx. Extranasopharyngeal lymphoepithellomas may be located in the stomach or digestive tract, and only one single case of esophageal location has been found in our review. In many cases the tumor is related to Epstein-Barr virus infection. We report a case of undifferentiated carcinoma of the distal third of the esophagus in a 79 year-old man. Pathological examination of the esophagus revealed an undifferentiated carcinoma with lymphold stroma (lymphoep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…LELC is one of the least common primary epithelial malignancies of the esophagus. Outside of Asia, the incidence of LELC is little more than anecdotal . The clinical presentation and gross appearance of this neoplasm are similar to those of conventional SCC.…”
Section: Rare Variants Of Squamous Carcinomamentioning
confidence: 89%
“…LELC is one of the least common primary epithelial malignancies of the esophagus. Outside of Asia, the incidence of LELC is little more than anecdotal . The clinical presentation and gross appearance of this neoplasm are similar to those of conventional SCC.…”
Section: Rare Variants Of Squamous Carcinomamentioning
confidence: 89%
“…However, Wang et al 24 failed to demonstrate, by 2 different methods (in situ hybridization for EBER-1 transcript and PCR amplification for EBV BamHI W region), the presence of EBV in 51 cases of tumors of the esophagus, including 12 with prominent lymphoid stroma reminiscent of LELC. Accordingly, Parra et al, 11 who reported the first LELC of the esophagus in Western countries, and Sashiyama et al 12 reporting a case from Japan did not demonstrate the presence of EBV using the above-mentioned methods. Taken together, it seems plausible that EBV infection is not associated with LELC of the esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, only 29 cases have been reported in the literature, including the present case. [6][7][8][9][10][11][12][13][14]22 The epidemiology of LELC is somewhat similar to squamous cell carcinoma (SCC) of the esophagus. 1,23 Both neoplasms are more prevalent in China and Southeast Asia and share associated risk factors such as alcohol and tobacco use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoepithelioma‐like carcinoma has been described in various organs including the salivary gland, thymus, thyroid, breast, lung, stomach, urinary bladder, uterine cervix and skin 3–11 . According to Medline's database ‘PubMed’, 16 LELC cases arising in the esophagus have been documented in the English literature 13–23 . This includes the cases described as poorly differentiated carcinoma with prominent lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 99%